Sur et pour... mais pas avec. Recherches doctorales sur le numérique en éducation - Jean-Luc Rinaudo (Université de Provence, 2020)
The author proposes a study of the abstracts of thesis on the digital of the doctors who submitted a dossier of qualification to the functions of lecturer, at the 70th section of the CNU, between 2015 and 2019. The analysis is conducted from the lexicon used in these abstracts. The heuristic focus is present, the critical focus rare. As for the praxeological aim, the author proposes that it be erased in favour of a pragmatic aim.